Does testosterone impair men's cognitive empathy? Evidence from two large-scale randomized controlled trials. Issue 1910 (4th September 2019) - Nadler, Amos; Camerer, Colin F.; Zava, David T.; Ortiz, Triana L.; Watson, Neil V.; Carré, Justin M.; Nave, Gideon
Abstract : The capacity to infer others' mental states (known as 'mind reading' and 'cognitive empathy') is essential for social interactions across species, and its impairment characterizes psychopathological conditions such as autism spectrum disorder and schizophrenia. Previous studies reported that testosterone administration impaired cognitive empathy in healthy humans, and that a putative biomarker of prenatal testosterone exposure (finger digit ratios) moderated the effect. However, empirical support for the relationship has relied on small sample studies with mixed evidence. We investigate the reliability and generalizability of the relationship in two large-scale double-blind placebo-controlled experiments in young men ( n = 243 and n = 400), using two different testosterone administration protocols. We find no evidence that cognitive empathy is impaired by testosterone administration or associated with digit ratios. With an unprecedented combined sample size, these results counter current theories and previous high-profile reports, and demonstrate that previous investigations of this topic have been statistically underpowered.